Copy number variations within fibroblast growth factor 13 gene influence growth traits and alternative splicing in cattle - Hanfang Cai; Xin Li; Xinran Niu; Jing Li; Xianyong Lan; Chuzhao Lei; Yongzhen Huang; Huifen Xu; Ming Li; Hong Chen (Animal Biotechnology)
Previous researches revealed a copy number variation (CNV) region in the bovine fibroblast growth factor 13 (FGF13) gene. However, its effects remain unknown. This study detected the various copy number types in seven Chinese cattle breeds and analysed their population genetic characteristics and effects on growth traits and transcription levels. Copy number Loss was more frequent in Caoyuan Red cattle and Xianan cattle than in the other breeds. Association analysis between CNV and growth traits of Qinchuan indicated that the CNV was significantly related to chest depth, hip width and hucklebone width (P < 0.05). Additionally, the growth traits of individuals with copy number Loss were significantly inferior to those with copy number Gain or Median (P < 0.05). Besides, we found two splicing isoforms, AS1 and AS2, in FGF13 gene, which resulted from alternative 5′ splicing sites of intron 1. These isoforms showed varied expression levels in various tissues. Moreover, CNV was significantly and negatively associated with the mRNA expression of AS1 (r = −0.525, P < 0.05). The CNVs in bovine FGF13 gene negatively regulated growth traits and gene transcription. These observations provide new insights into bovine FGF13 gene, delivering potentially useful information for future Chinese cattle breeding programs.